Electrical Conductivity Versus Temperature in Freezing Conditions: A Field Experiment Using a Basket Geothermal Heat Exchanger. Issue 24 (17th December 2019) - Coperey, A.; Revil, A.; Stutz, B.
Abstract: We use a basket geothermal heat exchanger during 518 hr to freeze a portion of soil. This field experiment is monitored using time lapse electrical conductivity tomography and a set of 47 in situ temperature sensors. A frozen soil core characterized by negative temperatures and low conductivity values (<10 −3 S/m) develops over time. A petrophysical model describing the temperature dependence of the electrical conductivity in freezing conditions is applied to the field data and compared to two laboratory experiments performed with two core samples from the test site. The results show that this petrophysical model can be used to interpret field measurements bridging electrical conductivity to temperature and liquid water content. Plain Language Summary: In order to better understand the evolution of permafrost (spatial extent, temperature, and liquid water content distributions), we can use time lapse electrical conductivity tomography. The electrical conductivity of a soil is influenced by water and ice contents, temperature, salinity of the pore water, and the cation exchange capacity of the material. We test a physics‐based relationship connecting temperature, ice content, and electrical conductivity. This relationship is tested on two core samples and compared with field observations during a in‐situ test experiment. In this experiment, we generated a frozen soil core using a geothermal heat exchanger, and at the same time, we recorded the temperature and electrical conductivity distributions. We found a good consistency between the field data and the model, which means that from the distribution of the electrical conductivity of the frozen soil, we are able to recover its temperature. Key Points: Electrical conductivity is related to temperature via a soil freezing curve Frozen ground is generated in the field using a geothermal heat exchanger Both field and laboratory experiments are consistent with the theory